Facile synthesis of biogenic silica nanomaterial loaded transparent tragacanth gum hydrogels with improved physicochemical properties and inherent anti-bacterial activity. Issue 32 (29th July 2022) - Verma, Mohini; Dar, Aqib Iqbal; Acharya, Amitabha
Abstract : Bowknot silica nanomaterials were isolated from Lantana camara . These were modified and used as sequester for the formation of tragacanth gum hydrogel with enhanced anti-bacterial property and further showed promising cell proliferation. Abstract : In this report, biogenic, crystalline (∼60.5 ± 2%) bowknot structured silica nanoparticles (BSNPs) of length ∼ 274 ± 7 nm and width ∼ 36 ± 2 nm were isolated from invasive species viz . Lantana camara . These were then chemically modified using nitrogen containing moieties viz . APTES and CTAB. These modified BSNPs were then used as electrostatic cross-linking agents for the formation of tragacanth gum (TG) hydrogels. The cytocompatible CTAB@BSNP-TG hydrogels documented ∼10–12 fold enhancement in anti-bacterial activity against Staphylococcus aureus and Pseudomonas aeruginosa when compared with TG hydrogels. Disruption of the bacterial membrane by ROS generation and protein leakage were responsible for anti-bacterial activity. A cell migration assay suggested that CTAB@BSNP-TG augmented the cell proliferation of NIH-3T3 cells compared to other TG hydrogels. The present study will pave the path for the development of organic–inorganic hybrid nanocomposite-based hydrogels for anti-bacterial and cell migration applications.